Effect of Post-Veraison Irrigation Level on Sauvignon blanc Yield, Juice Quality and Water Relations - Naor, A.; Bravdo, B.; Hepner, Y. (South African Journal of Enology and Viticulture, 2017)
Low (L), medium (M) and high (H) post-veraison daily irrigation levels (1 mm, 2 mm and 3,5 mm, respectively) were applied in a Sauvignon blanc vineyard in the Golan Heights of Israel. Juice Brix levels were higher in the H treatment than in the L treatment. Yields were higher in H treatment than in L treatment in years with high crop level. Shoot elongation ceased at veraison in all three treatments. Average midday leaf water potential (LWP) was -1,4 MPa and -1,9 MPa in the Hand L treatments, respectively. Lower stomata! resistance (R,J was found in the H treatment compared to those in the L and M treatments. A negative correlation between Rs and LWP was observed. Leaf temperatures were higher in the L treatment than in the H treatment. This was mainly attributed to the difference in Rs between treatments. The apparent relationship between R8 and LWP suggests the use of canopy heat balance for irrigation management in warm regions, provided that satisfactory methodologies for boundary-layer resistance and the evaluation of net radiation in vineyards are developed.